#TITLE_ALTERNATIVE# - WICAKSONO (NIM : 15108034); PEMBIMBING : Dr. Akhmad Riqqi, M.Si. ; Dr. Ir. Agung Budi Harto, , AMRI
Micro-Hydro Power Plant (MHPP) is a kind of technology that could independently supplies electricity to an area. West Java, with its topographic condition as it has quite a lot of watershed, is a potential area to build MHPP. This GIS-based modeling is executed as an approach to determine monthly potential power in specific locations in West Java. The modeling utilized the calculation of MHPP potential power by using the head and the discharge of the watershed. The value of a watershedÃ‚Â’s head will be modeled using Digital Elevation Model (DEM) data that was obtained from Shuttle Radar Topography Mission (SRTM) 90 M data in the area of West Java, while the value of the discharge was obtained from the Rational Method calculation that will result the value of the discharge in an outlet for every time unit. Obtained from this study are the 37 potential MHPP points in West Java. The most potential location to build an MHPP is located in the geodetic coordinate of 107.8346 E ; 6.68285 S.